Factores psicosociales en la nutrición del adulto mayor del Centro Gerontológico Hogar San José - Solano Chamba, Eufemia Elizabeth (2022)
Psychosocial factors such as depression, family coexistence, harmful habits influence the risk of malnutrition in the elderly because it is fragile and requires care to maintain a good lifestyle. The aim of this study was to relate psychosocial factors with the nutrition of older adults in the Gerontological Center Hogar San José, it was a descriptive, quantitative, crosssectional study, the universe was made up of 49 older adults. The personal interview was used as a technique and as an instrument a questionnaire validated by Sanango 2017, the results showed that 77.6% are in the fourth age, 51% are women, 59.2% do not have educational instruction and 69.4% are single; among psychosocial factors it was found that 51% do not receive family visits, 21% have mild and severe family dysfunction, 100% do not have any depressive state, 63% do not perform any physical activity, 100% do not use tobacco or alcohol and as for body mass index 67.3% have thinness. Finally, no relationship was found between psychosocial factors and the nutrition of the elderly. In conclusion, although psychosocial factors were not related to nutrition, it was evidenced that in older adults in a state of thinness, most of them do not perform physical activity and do not receive family visits which would be a risk factor for malnutrition